QUO VADIS: DINAMIKA POLITIK HUKUM PENGESAHAN UNDANG UNDANG PERAMPASAN ASET - Purba, Paulus (Jurnal Perspektif Hukum, 2024)
The recovery of assets derived from crimes has become one of the urgent and critical issues at the global level in Indonesia, namely to take back assets illegally obtained by and or who are not legally responsible so that the Government and the DPR based on their authority need to ratify the draft law on asset forfeiture immediately into law. The formulation of the problem in this study is How are the dynamics of legal politics in the formation of the draft law on asset forfeiture based on Law Number 13 of 2022 concerning the Formation of Legislation. The research method used is normative juridical law or library legal research (search library), by analysing literature or secondary data relevant to the topic. This research is descriptive analytical, the data obtained and processed and analysed to provide a comprehensive picture of the legal political dynamics that occur between the Government and the DPR in terms of passing the draft law on asset forfeiture into law, with data collection methods through document studies. The results showed that the legal political dynamics that occurred between the Government and the DPR so that the Asset Forfeiture Bill was not passed due to many things, including first: The Asset Forfeiture Bill is contrary to Law Number 39 of 1999 concerning Human Rights Article 29 Paragraph (1); Second. Political interests of the Government and Parliament; Third. Coordination issues between law enforcement agencies; Fourth. The authority to adjudicate in the judicial system